Excessive Daytime Sleepiness in Obstructive Sleep Apnea Patients Treated With Continuous Positive Airway Pressure: Data From the European Sleep Apnea Database - Maria R. Bonsignore; Maria R. Bonsignore; Jean L. Pepin; Fabio Cibella; Calogero D. Barbera; Oreste Marrone; Johan Verbraecken; Tarja Saaresranta; Tarja Saaresranta; Ozen K. Basoglu; Georgia Trakada; Izolde Bouloukaki; et al. (Frontiers in Neurology, 2021)
Excessive daytime sleepiness (EDS) is a symptom of obstructive sleep apnea (OSA) that resolves under treatment with continuous positive airway pressure (CPAP). In some patients, sleepiness persists despite CPAP treatment. We retrospectively analyzed data on subjective residual EDS, assessed as an Epworth Sleepiness Scale score (ESS) >10, in patients from the European Sleep Apnea Database (n = 4,853, mean age ± SD 54.8 ± 11.8 years, 26.1% females), at baseline and at the first visit (median follow-up: 5 months, interquartile range 3–13). An ESS > 10 occurred in 56% of patients at baseline and in 28.2% of patients at follow-up. Residual EDS was analyzed in 2,190 patients (age: 55.1 ± 12.0 years, 26.1% females) with sleep monitoring data (median follow-up: 3 months, interquartile range 1–15). Sleep studies during CPAP use were obtained in 58% of these patients; EDS was reported by 47.2% of patients at baseline and by 30.3% at follow-up. Residual OSA, defined as an apnea–hypopnea index >10/h, and insufficient CPAP adherence, defined as nightly use <4 h, occurred with similar frequency in patients with and without EDS at follow-up. Prevalence of residual EDS was highest (40%) in patients with a first follow-up visit at 0–3 months, then it was 13–19% in patients with a first follow-up visit after 4 months to 2 years. The change in ESS (n = 2,190) was weakly correlated with CPAP use (R2 = 0.023, p < 0.0001). Logistic regression showed that an ESS score >10 at the first follow-up visit was associated directly with ESS at baseline and inversely with duration of follow-up, and CPAP use (R2 of the model: 0.417). EDS showed heterogeneity in different European countries both at baseline and at the first follow-up visit, suggesting modulation by cultural and lifestyle factors. In conclusion, residual EDS in CPAP-treated OSA occurred in approximately one in four patients at follow-up; its prevalence was highest (40%) in the first 3 months of treatment and subsequently decreased. The finding of residual EDS in a significant percentage of optimally treated OSA patients suggests that wake-promoting agents may be useful, but their indication should be evaluated after at least 3 months of treatment.